Revision of Recurrent Hallux Valgus Deformity Using a Percutaneous Distal Transverse Osteotomy: Surgical Considerations and Mean 3.6 Year Results - Thomas L. Lewis BSc (Hons) MBChB (Hons) FRCS (Tr&Orth) MFSTEd; Robbie Ray MBChB, ChM(T&O), FRCSed(Tr&Orth) FEBOT; Evelyn Murphy MBBCh BAO MCh FRCS (Tr & Orth); Min Jia Chua MB BS FRCSEd; Clare Watt BNurs; Peter Lam MBBS (Hons), FRACS, FAOA (Foot & Ankle Orthopaedics)
Category: Bunion; Lesser Toes Introduction/Purpose: Hallux Valgus (HV) is a common forefoot deformity that can cause pain and difficulty with walking. There are a range of surgical techniques to treat HV deformity, but there is a risk of recurrence. This paper reviews the clinical assessment and management of recurrent HV as well as a detailed description of how percutaneous surgical techniques can be used to treat recurrent HV. This paper identifies technical challenges of percutaneous HV surgery for recurrent HV deformity as well as strategies to address and mitigate these. Methods: This was a multicenter retrospective review of adult patients who had recurrent hallux valgus deformity (defined as hallux valgus angle>15° and having previously undergone primary surgical intervention for HV deformity correction) who were treated with a percutaneous metatarsal extra-capsular transverse osteotomy (META) technique between 5/12/2013 and 8/1/2022, with at least one year of follow-up data. Demographic information, hallux valgus angle, 1-2 intermetatarsal angle, Manchester-Oxford Foot Questionnaire (MOXFQ;validated for hallux valgus surgery), visual analog scale (VAS), and EQ-5D-5L scores were collected. All p-values < 0.05 were considered significant. Results: We retrospectively evaluated 34 feet from 32 patients with a mean age of 63.1±9.2 (range 41-82) who underwent revision hallux valgus surgery using a percutaneous technique. The mean follow up was 3.6±2.3 (range 0.5-8.7 years. The breakdown of index HV surgeries was: 17 Chevron, 9 Scarf/Akin, 6 medial bunionectomy, 1 Lapidus, 1 proximal rotation osteotomy. There was a statistically significant improvement in both clinical foot function and radiographic deformity after surgery. The mean hallux valgus angle decreased from 32.9±8.6° to 13.4±7.3°, and the intermetatarsal angle decreased from 12.7±3.8° degrees to 3.8±3.1°(p< 0.05). The mean MOXFQ Index score significantly improved from 49.4±23.1 to 14.6±19.4 (p< 0.05). Conclusion: This paper suggests that percutaneous surgical techniques using a transverse osteotomy and screw fixation can successfully treat a wide range of recurrent HV deformity severities with significant improvement in clinical and radiographic outcomes.